2019
DOI: 10.1021/acs.jpcc.9b00864
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Electrical Conductivity of Associated Lithium Salts in Solvents for Lithium–Air Batteries

Abstract: The choice of optimal electrolytes is crucial for improving the electrochemical performance of a lithium air battery because it determines the morphology of the discharge products in the cathode and the conductivity of the electrolyte. We have critically analyzed an important aspect related to the behavior of highly associated electrolytes, as those used in lithium−air batteries: the prediction of the concentration of maximum conductivity. Lithium triflate and lithium bis(trifluoromethyl sulfonyl)imide in glym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…We remark herein that viscosity and Li + transference number measurements on solutions using either G 1 or G 2 and either LiTf or LiTFSI have suggested a failure of the Walden's rule, in spite of a qualitative correlation with the association constant of the salts. 126 The electrolyte composition may affect crucial parameters for applications in a Li-O 2 battery using a carbon-cloth GDL, such as the conductivity, viscosity, contact angle, and decomposition temperature. Among various formulations, the G 4 -LiTFSI was often selected as the electrolyte of choice due to its suitable properties for use in the open metal-oxygen cell design.…”
Section: Greenmentioning
confidence: 99%
See 2 more Smart Citations
“…We remark herein that viscosity and Li + transference number measurements on solutions using either G 1 or G 2 and either LiTf or LiTFSI have suggested a failure of the Walden's rule, in spite of a qualitative correlation with the association constant of the salts. 126 The electrolyte composition may affect crucial parameters for applications in a Li-O 2 battery using a carbon-cloth GDL, such as the conductivity, viscosity, contact angle, and decomposition temperature. Among various formulations, the G 4 -LiTFSI was often selected as the electrolyte of choice due to its suitable properties for use in the open metal-oxygen cell design.…”
Section: Greenmentioning
confidence: 99%
“…We remark herein that viscosity and Li + transference number measurements on solutions using either G 1 or G 2 and either LiTf or LiTFSI suggested a failure of Walden's rule, in spite of a qualitative correlation with the association constant of the salts. 126…”
Section: “Glyme Electrolyte” In a Li–o2 Battery: The Upcoming Futurementioning
confidence: 99%
See 1 more Smart Citation
“…Horwitz G. et al [30] fundamentally analysed a significant viewpoint identified with the conduct of profoundly related electrolytes, as those utilized in lithium−air batteries. As a model of electrolytes with solid ionic grouping, lithium triflate and lithium bis(trifluoromethylsulfonyl)imide were used in monoglyme and diglyme.…”
Section: Overview Of Various Solvents and Electrolytes Used In Energy...mentioning
confidence: 99%
“…[45,46] Thus, it was restated to a comparable specific conductivity quantity, called molar conductivity ( Figure 3). [47,48] The value of molar conductivity is equivalent to the conductance caused by all the mobile ionic charge-carriers in the solution reduced to 1 M concentration, but for the same volume (cm 3 ) in-between the electrodes (area 1 cm 2 and 1 cm apart).…”
Section: Impact Of Reduction In Operating Temperature On Catholyte's mentioning
confidence: 99%